2006
DOI: 10.1534/genetics.105.053538
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Adaptive Trait Introgression BetweenIris fulvaandI. brevicaulisin Highly Selective Field Conditions

Abstract: The idea that natural hybridization has served as an important force in evolutionary and adaptive diversification has gained considerable momentum in recent years. By combining genome analyses with a highly selective field experiment, we provide evidence for adaptive trait introgression between two naturally hybridizing Louisiana Iris species, flood-tolerant Iris fulva and dry-adapted I. brevicaulis. We planted reciprocal backcross (BC 1 ) hybrids along with pure-species plants into natural settings that, due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
205
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(214 citation statements)
references
References 71 publications
7
205
1
1
Order By: Relevance
“…Natural selection can cause fixation of advantageous alleles that have a positive fitness effect and potential to speed up adaptation in new genetic background of hybrids (De Carvalho et al 2010;Martin et al 2006). Two loci in our hybrid dataset showed increased frequency towards alleles specific to P. sylvestris at calcium-dependent protein kinase (Pr4-5) and alleles specific to P. mugo at mys transcription factor (Pr4-10).…”
Section: Discussionmentioning
confidence: 86%
“…Natural selection can cause fixation of advantageous alleles that have a positive fitness effect and potential to speed up adaptation in new genetic background of hybrids (De Carvalho et al 2010;Martin et al 2006). Two loci in our hybrid dataset showed increased frequency towards alleles specific to P. sylvestris at calcium-dependent protein kinase (Pr4-5) and alleles specific to P. mugo at mys transcription factor (Pr4-10).…”
Section: Discussionmentioning
confidence: 86%
“…Quéré et al. (2012) suggested that WEM was possibly a “hybrid swarm.” One of those features is the observation of increased fitness that should allow for ecological success to translate into evolutionary success (see, e.g., Pereira et al., 2014 for a marine example)—which could reflect adaptive introgression promoting the maintenance of hybrids (Hedrick, 2013; Martin, Bouck, & Arnold, 2006). Patterns of survival of the WEM × WEM cross go against high fitness of these “hybrids.” Adaptive introgression patterns or “swarming” at the center of the distribution of parental forms seems relatively common in other fish species (e.g., Machado‐Schiaffino, Juanes, & Garcia‐Vazquez, 2010; Roques, Sévigny, & Bernatchez, 2001; Sinama et al., 2013; Stemshorn, Reed, Nolte, & Tautz, 2011; Walters et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Introgressed alleles may often have a positive fitness effect in their new genetic background and traits responsible for adaptation can be transferred between species (Martin et al 2006). Foreign alleles in different genetic or ecological backgrounds will show a range of fitness outcomes, but only those that increase the adaptive optimum in a given environment will effectively introgress.…”
Section: Discussionmentioning
confidence: 99%